REVERSE LOGISTICS OF PESTICIDE PACKAGING - Tedesco, Isabelle Mirella (Revista Interface Tecnológica, 2025)
Reverse logistics of pesticide packaging is a mandatory system in Brazil, regulated by law, which aims to collect, return and properly dispose of these packaging to minimize environmental impacts and protect public health. It involves shared responsibility between manufacturers, retailers, farmers and government. The packaging is collected, cleaned and sent for recycling or incineration, preventing soil and water contamination. The article analyzes the factors that contributed to the creation of this responsibility network, highlighting the role of each actor in consolidating the system as a reference in sustainability.
Keywords: Reverse Logistics; Responsibility; Pesticides; Lead Time